2023
DOI: 10.1093/nar/gkad048
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel 5-aminomethyl-2-thiouridine methyltransferase in tRNA modification

Abstract: The uridine at the 34th position of tRNA, which is able to base pair with the 3′-end codon on mRNA, is usually modified to influence many aspects of decoding properties during translation. Derivatives of 5-methyluridine (xm5U), which include methylaminomethyl (mnm-) or carboxymethylaminomethyl (cmnm-) groups at C5 of uracil base, are widely conserved at the 34th position of many prokaryotic tRNAs. In Gram-negative bacteria such as Escherichia coli, a bifunctional MnmC is involved in the last two reactions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 75 publications
4
11
0
Order By: Relevance
“…Bioinformatic analysis shows the occurrence of diverse biochemical strategies for hypermodification of U34 in tRNA Glu, Gln, Lys in bacteria. Our results from the S. mutans and S. pneumoniae ΔmnmM strains confirm the functional assignment of Cho et al (22) that MnmM is required in the SAM-dependent methylation reaction nm 5 s 2 U to form mnm 5 s 2 U. Our analysis from B. subtilis ΔmnmM, however, did not show the same requirement, suggesting that, in this organism, other methylases may provide functional replacement under certain growth conditions.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Bioinformatic analysis shows the occurrence of diverse biochemical strategies for hypermodification of U34 in tRNA Glu, Gln, Lys in bacteria. Our results from the S. mutans and S. pneumoniae ΔmnmM strains confirm the functional assignment of Cho et al (22) that MnmM is required in the SAM-dependent methylation reaction nm 5 s 2 U to form mnm 5 s 2 U. Our analysis from B. subtilis ΔmnmM, however, did not show the same requirement, suggesting that, in this organism, other methylases may provide functional replacement under certain growth conditions.…”
Section: Discussionsupporting
confidence: 87%
“…The genomic co-localization of ytqA and mnmM observed in S. mutans is also observed in B. subtilis . Recently, MnmM has been identified as the SAM-dependent methyltransferase catalyzing the final step in mnm 5 s 2 U synthesis (22) In this report, Cho et showed that nmnM inactivation resulted in the loss of mnm 5 s 2 U with concomitant accumulation of nm 5 sU, a phenotype similar to that of S. mutans . However, earlier studies from the Armengod laboratory had shown that inactivation of mnmM ( ytqB ) does not eliminate the synthesis of mnm 5 s 2 U tRNA (20).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations